How reliable are AI-Assisted cephalometric programs in assessing measurements involving bilateral landmarks? - Gurel Hakan Gurcan; Alkumru Pinar; Sectakof Pavel (Australasian Orthodontic Journal, 2025)
Recent advancements in technology have promoted artificial intelligence (AI) to automatically detect landmarks on lateral cephalograms. This study aimed to evaluate the reliability of an AI-assisted cephalometric analysis program (Webceph, Gyeonggi-do, Republic of Korea) in the assessment of cephalometric measurements involving bilateral landmarks.